Influence of Eastern redcedar oil on enzymatic hydrolysis of microcrystalline cellulose and Saccharomyces cerevisiae fermentations - Ramachandriya, Karthikeyan D.; Dunford, Nurhan T.; Atiyeh, Hasan K.; Hiziroglu, Salim; Wilkins, Mark R. (Biocatalysis and agricultural biotechnology, 2014)
Essential oils from plants are known to be inhibitory to yeast and amylase activity. This study investigated the effects of oil in Eastern redcedar (Juniperus virginiana L.) on enzymatic cellulose hydrolysis and yeast fermentation for ethanol production from redcedar. Enzymatic hydrolysis was conducted with 2% and 4% (w/w) cellulose loadings, 25FPU/g cellulose and 50FPU/g cellulose enzyme loadings (Accelerase® 1500) and 0%, 0.5% and 1% (w/w) redcedar oil loadings. The presence of 0.5% and 1% (w/w) redcedar oil inhibited cellulose-to-glucose yields by 26% and 33% and inhibited cell growth and ethanol production by Saccharomyces cerevisiae during the first 9h. Similar ethanol concentrations of up to 22g/l (92% of theoretical yield) were produced with all treatments within 12h. The results of this study suggest that redcedar oil be removed prior to enzymatic hydrolysis and fermentation for efficient ethanol production using redcedars. •Eastern redcedar oil inhibited ethanol fermentation by S. cerevisiae.•Eastern redcedar oil inhibited cellulase hydrolysis by cellulase.•Volatile oil must be removed from redcedar to use it for ethanol production.